2015
DOI: 10.1136/bmjquality.u209890.w4102
|View full text |Cite
|
Sign up to set email alerts
|

Improving fluid balance monitoring on the wards

Abstract: Clinical experience and nursing metrics have consistently identified poor documentation of fluid balance monitoring at Milton Keynes University Hospital, compromising patient safety and quality of care. This project aimed to increase the percentage of fluid balance charts correctly completed on the wards.Three areas for improvement were identified: understanding the importance of good fluid balance monitoring, correct identification of patients requiring monitoring, and ease of completion of fluid balance char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…It is necessary to know the exact measures of urine, drainage and vomiting output for quality treatment. Such information is also important to prevent the patients from complications like fluid overload (Jeyapala, Gerth, Patel, & Syed, 2015). Similarly, the study noted that fluid monitoring improves the practices of accurate fluid balance documentations (Scales & Pilsworth, 2008).…”
Section: Literature Reviewmentioning
confidence: 81%
“…It is necessary to know the exact measures of urine, drainage and vomiting output for quality treatment. Such information is also important to prevent the patients from complications like fluid overload (Jeyapala, Gerth, Patel, & Syed, 2015). Similarly, the study noted that fluid monitoring improves the practices of accurate fluid balance documentations (Scales & Pilsworth, 2008).…”
Section: Literature Reviewmentioning
confidence: 81%
“…Furthermore, close to half (145, 49.5%) of women were identified as euvolemic, which seems to be contrary to the fact that most participants were tolerating oral fluids and food until the point of epidural commencement (228, 77.8%); and an additional 106 (36%) already had “maintenance IV fluids” also running. Although fluid balance charts are used internationally to document input and output (Jeyapala, Gerth, Patel, & Syed, ), we identified poor compliance with documentation of rationale for IV fluid administration by midwifery and medical staff. Midwives need to ensure that evidence‐based guidelines underpin their clinical practice to promote and ensure safe practice, reduce adverse events and standardize clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar project conducted in Milton Keynes Hospital, less than 45% of the charts surveyed were correctly filled, preintervention. 5 The study also found that many patients who did not necessarily need fluid balance monitoring were being monitored. In Central Manchester University Hospitals National Health Service (NHS) Foundation Trust, the Fluid Balance Improvement Project found that only 30% of the charts met their criteria for completion and accuracy.…”
Section: Problemmentioning
confidence: 95%